ANALISIS KESALAHAN SISWA SMP DALAM MENYELESAIKAN SOAL MATERI SISTEM PERSAMAAN LINIER DUA VARIABEL BERDASARKAN TAKSONOMI BLOOM DENGAN MENGGUNAKAN TEORI POLYA - Sugiarto, Almira Nurfarisi; Afrilianto, M. (IKIP Siliwangi, 2021)
This study aims to identify and describe student errors in working on a two-variable system of linear equations in class VIII SMP students. This study uses a qualitative descriptive research with a description test instrument consisting of 3 questions using the level of thinking ability Bloom's Taxonomy, namely, C3 represents middle-level ability and C4 and C5 represents higher-order thinking ability. The subjects in this study were 17 students of class VIII of one of the public junior high schools in West Bandung Regency. This study uses Polya's analytical theory to interpret the results of the data presented in the form of a percentage based on the stages of difficulty in solving story problems. The results of this study show that the interpretation of the difficulties experienced by students in getting interpretations at the Bloom Taxonomy level C3 is good, C4 and C5 is lacking, with errors that are influenced by student errors, namely: conceptual errors, errors in translating story questions, incomplete mastery of material, mistakes in steps. solutions and errors in calculations.